2022
DOI: 10.21511/imfi.19(4).2022.02
|View full text |Cite
|
Sign up to set email alerts
|

Cost of capital and firm value: Evidence from Indonesia

Abstract: Cost and capital structure are needed to evaluate the feasibility of the investments made by a company. This study aims to estimate and analyze the effect of the component of cost of capital (COC) and capital structure (CS) on firm value. Pulp & Paper companies listed on the Indonesia Stock Exchange (IDX) became the research sample for the 2013–2020 period. The research method applied is a moderation regression analysis approach. The empirical findings of the study prove that firm value is not infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…However, in the case of negative effect, the findings of this study are consistent with the results of some previous studies, including Majumdar and Chhibber (1999), Gleason et al (2000), Le and Phan (2017), Vo and Ellis (2017), and Qayyum and Noreen (2019). Moreover, in the case of both the positive and negative effects of both leverage and capital structure on financial performance, the findings in our paper support the findings in Bandyopadhyay and Barua (2016), Jaisinghani and Kanjilal (2017), Endri, Ridho, et al (2021), Endri, Supeni, et al (2021), andKurniasih et al (2022).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, in the case of negative effect, the findings of this study are consistent with the results of some previous studies, including Majumdar and Chhibber (1999), Gleason et al (2000), Le and Phan (2017), Vo and Ellis (2017), and Qayyum and Noreen (2019). Moreover, in the case of both the positive and negative effects of both leverage and capital structure on financial performance, the findings in our paper support the findings in Bandyopadhyay and Barua (2016), Jaisinghani and Kanjilal (2017), Endri, Ridho, et al (2021), Endri, Supeni, et al (2021), andKurniasih et al (2022).…”
Section: Discussionsupporting
confidence: 92%
“…The authors find that liquidity, profitability, and oil prices negatively affect leverage, while companies' size does not impact leverage. Kurniasih et al (2022) analyse the effect of the cost of capital and capital structure on firm value. It documents that the cost of debt (COD) and cost of equity (COE) negatively and positively affect firm value.…”
Section: Related Work On Capital Structure and Firm Performancementioning
confidence: 99%
“…They reported no moderation effect of interest rate.In contrast, Hussain et al [27] reported that firm size and interest rate are good moderators of capital structure. Kurniasih and Rustam [28] examined the influence of CS as a moderator between the cost of capital and FV in Indonesian companies. They found a quasi-role of capital structure as a moderator.…”
Section: Other Moderation Effectsmentioning
confidence: 99%
“…The company will choose the next source of funding from debt where the debt has a lower risk compared to issuing new shares (Fama and French, 2002). Besides having benefits such as tax protection, choosing debt as a source of funding can also increase the company's net profit (Kurniasih et al, 2022). The increasing net profit has an impact on the increase in stock prices and company value.…”
Section: Panel Data Regression Model Estimationmentioning
confidence: 99%